Progesterone exerts a neuroprotective action in a Parkinson’s disease human cell model through membrane progesterone receptor α (mPRα/PAQR7) - Castelnovo, Luca F.; Thomas, Peter (Frontiers in Endocrinology, 2023)
Parkinson’s disease (PD) is the second most common neurodegenerative disease worldwide, and current treatment options are unsatisfactory on the long term. Several studies suggest a potential neuroprotective action by female hormones, especially estrogens. The potential role of progestogens, however, is less defined, and no studies have investigated the potential involvement of membrane progesterone receptors (mPRs). In the present study, the putative neuroprotective role for mPRs was investigated in SH-SY5Y cells, using two established pharmacological treatments for cellular PD models, 6-hydroxydopamine (6-OHDA) and 1-methyl-4-phenylpyridinium (MPP+). Our results show that both the physiologic agonist progesterone and the specific mPR agonist Org OD 02-0 were effective in reducing SH-SY5Y cell death induced by 6-OHDA and MPP+, whereas the nuclear PR agonist promegestone (R5020) and the GABAA receptor agonist muscimol, were ineffective. Experiments performed with gene silencing technology and selective pharmacological agonists showed that mPRα is the isoform responsible for the neuroprotective effects we observed. Further experiments showed that the PI3K-AKT and MAP kinase signaling pathways are involved in the mPRα-mediated progestogen neuroprotective action in SH-SY5Y cells. These findings suggest that mPRα could play a neuroprotective role in PD pathology and may be a promising target for the development of therapeutic strategies for PD prevention or management.